2016
DOI: 10.1371/journal.pone.0152255
|View full text |Cite
|
Sign up to set email alerts
|

Communication at the Garden Fence – Context Dependent Vocalization in Female House Mice

Abstract: House mice (Mus musculus) live in social groups where they frequently interact with conspecifics, thus communication (e.g. chemical and/or auditory) is essential. It is commonly known that male and female mice produce complex vocalizations in the ultrasonic range (USV) that remind of high-pitched birdsong (so called mouse song) which is mainly used in social interactions. Earlier studies suggest that mice use their USVs for mate attraction and mate choice, but they could also be used as signal during hierarchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Yet, because social approach precedes adult‐initiated partner sniffing, the lack of tighter correlation of these aspects of sociability across strains was somewhat unexpected. The expression of social behaviors depends importantly upon the interplay between the magnitude of internal social drives and the specific social (eg, age, sex, familiarity of the partner) and environmental (familiarity, safety, size) context . Thus, we suggest that rank‐order variation across tasks is likely because of important task differences, including differences in partner attributes (juvenile, adult), behavioral requirements (chamber exploration, presence of novel objects), and ethological relevance of behaviors (direct interaction vs restricted partner access).…”
Section: Discussionmentioning
confidence: 93%
“…Yet, because social approach precedes adult‐initiated partner sniffing, the lack of tighter correlation of these aspects of sociability across strains was somewhat unexpected. The expression of social behaviors depends importantly upon the interplay between the magnitude of internal social drives and the specific social (eg, age, sex, familiarity of the partner) and environmental (familiarity, safety, size) context . Thus, we suggest that rank‐order variation across tasks is likely because of important task differences, including differences in partner attributes (juvenile, adult), behavioral requirements (chamber exploration, presence of novel objects), and ethological relevance of behaviors (direct interaction vs restricted partner access).…”
Section: Discussionmentioning
confidence: 93%
“…We observed that USVs emitted during intense social interactions were longer, harsher, more modulated, and showed more frequency jumps than USVs emitted during non-social behaviors or at the end of social contacts (Figures 3-4). This is reminiscent of USVs emitted by wild house mice during social contact, which are longer than USVs emitted when standing alone (near a food spot, in the nest) (Hoier et al, 2016b).…”
Section: Discussionmentioning
confidence: 96%
“…An ethological approach to mouse social communication should provide behavioral observations in contexts closer to natural conditions in which the animals should also be less stressed (Peromyscus californicus, P. boylii: (Briggs and Kalcounis-Rueppell, 2011;Kalcounis-Rueppell et al, 2006; Mus musculus: (Hoier et al, 2016a)). Here, we provide a detailed description of the spontaneous behaviors (see Table I in the Methods section) that are synchronized with USVs during an undisturbed period of three days and nights ( Figure 1a) at three different ages (5 weeks and 3 and 7 months).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, USVs including lower frequency (40–50 kHz) elements and frequency jumps are more attractive to female mice compared to USVs without these features [63]. The increasing numbers of studies reporting vocalizations between male-male and female-female mouse pairs suggests that vocalizations serve a social signaling role outside of opposite-sex interaction, however [45,61,62,64]. …”
Section: Discussionmentioning
confidence: 99%